Atypical Teratoid Rhabdoid Tumor of the Pineal Region in a 33-Month-Old Child: A Case Report - MACIAS GRAGEDA, MICHELLE ALEJANDRA; Montenegro Salcedo , Jorge Andres; Rodríguez Ruiz , Jorge Alejandro; Sánchez Terán , Alfonso; García Gonzalez, Oscar; Lozada Hernandez, Edgard (International Journal of Innovative Research in Medical Science, 2023)
Purpose: The present article describes a patient with an atypical teratoid/rhabdoid tumor of the pineal region and a literature review about this uncommon pathology. Methods: Literature review about Atypical Teratoid Rhabdoid Tumor between March and July of 2023 using 7 databases: Web of Science, Pubmed, Cochrane Library, SCOPUS, Science Direct, Clinical key and Medscape. Clinical features: A 33-month-old patient with an Atypical Teratoid Rhabdoid Tumor (ATRT) of the pineal region presented headache, VI cranial nerve paralysis, bilateral ataxia and loss of sphincters control during 3 months. Intervention: Endoscopic ventriculostomy with biopsy that reported ATRT. Conclusions: Recent statistics show that this tumor has been underdiagnosed throughout the time and evaluation of surgical material by a neuropathologist is required for its correct diagnosis.